Increasing and maintaining rates of standardized depression screening in youth with childhood-onset systemic lupus erythematosus in a pediatric rheumatology clinic - Emily Datyner; Jodi Dingle; Victoria Newsome; Lisa H. Buckley; Natasha Belsky; Seungweon Park; Manda Mitchell; Brooke Fine; Barron Patterson; T. Brent Graham; Alaina Davis (Pediatric Rheumatology Online Journal)
Abstract Background Depression adversely affects health outcomes in patients with childhood-onset systemic lupus erythematous (cSLE). By identifying patients with depressive symptoms, we can intervene early with referrals to mental health resources and improve outcomes. The aim of our quality improvement project was to increase and maintain rates of standardized depression screening for youth with cSLE seen within our pediatric rheumatology clinic. Methods Patients with cSLE 12 years of age or older seen for routine follow-up at our pediatric rheumatology clinic from September 16, 2019, through December 30, 2022, were offered the Patient Health Questionnaire-9 modified for adolescents (PHQ-A) to screen for depressive symptoms. A multidisciplinary team developed a key driver diagram to plan potential interventions to improve rates of screening. Plan‒Do‒Study‒Act (PDSA) cycles were used to prepare, implement, and evaluate interventions. Notable interventions focused on accurately identifying eligible patients, facilitating bidirectional communication between staff, and integrating and automating screening within the electronic health record (EHR). Statistical process control (SPC) methods were used for data analysis. Results The percentage of eligible patient encounters where depression screening was completed increased from 0 to 81% and was maintained for more than 6 months. This represents special cause variation, as evidenced by data shifts on our statistical process control chart. Among the 592 patients who completed depression screens, 114 (17%) were positive for moderate to severe symptoms, and 59 (9%) were positive for suicidal ideation (SI). Conclusions A high rate of standardized depression screening for youth with cSLE was achieved and maintained via integration and automation within our EHR. Establishing a highly reliable screening system is a critical first step in improving mental health care for this vulnerable population of youth.